Synergistic Effects of Deep Rotary Tillage and Microbial Decomposition Agents on Straw Decomposition, Soil Nutrient Dynamics, and Microbial Communities in Rice Systems - Xinyue Wang; Jie Huang; Yanting Tan; Lili Yang; Yuanhuan Li; Bing Xia; Hailin Li; Xiaohua Deng (Agriculture)
This study evaluated the synergistic effects of microbial decomposition agents and deep rotary tillage on rice straw decomposition, soil nutrient dynamics, and microbial communities in paddy fields of southern China. A two-factor randomized block experiment was conducted, with straw decomposition dynamics modeled using a modified Olson decay model, and microbial communities were assessed via high-throughput sequencing and network analysis. The combined treatment significantly increased the decomposition rate constant, reduced the time for 50% decomposition to 81 days, and enhanced soil nutrient availability, especially total nitrogen, phosphorus, and potassium. Microbial richness, diversity, and network complexity were also improved. Structural equation modeling indicated that nutrient availability, rather than microbial α-diversity, was the main driver of decomposition processes. These findings suggest that integrating microbial agents with deep tillage offers an effective strategy for optimizing straw return, improving soil fertility, and enhancing microbial functional resilience in rice systems.